ENHANCING EFFICIENCY AND PRODUCTIVITY USING AUTOMATION-PROGRAMMABLE LOGIC CONTROLLERS (PLC) - Eng. Abdulrahman Abed Salim Altaiy (Journal Park Publishing, 2024)
As the world of manufacturing evolves, it has become increasingly important to optimize processes to meet modern market demands. One solution that has increased in popularity is PLC automation. PLC automation uses industrial computers to automate repetitive tasks on a production line. This technology can be used for various purposes, including quality control and data processing. Programmable Logic Controller (PLC) automation has become an essential component of modern manufacturing, with many companies using it to enhance their productivity and efficiency. From reducing labor costs to improving product quality, PLC automation has many benefits that have helped it become an integral part of the manufacturing process. PLC automation enables organizations to improve their production processes, leading to increased efficiency, which can lead to reduced downtime and improved productivity, leading to increased profitability. Automation can also reduce labor costs and remove the need for manual work, which may be expensive and time-consuming. This can lead to significant cost savings over time. PLC automation also improves the quality of products by reducing the risk of errors and inconsistency, which can lead to increased customer satisfaction. Automation can also be customized to meet the specific needs of the organization. This can enable organizations to quickly adapt to changing market conditions and customer requirements, and automation can improve employee safety by reducing the risk of accidents and injuries. This can lead to a safer work environment and reduce the organization's liability. PLC automation allows organizations to collect and analyze data related to their production processes. This can provide many benefits to help organizations improve production efficiency, reduce costs, and increase profitability. By taking advantage of automation technology, organizations can remain competitive in today's fast-paced business environment and our country, Iraq, in particular.